IMPLEMENTATION OF MEDIA PHYSIC EDUCATION TECHNOLOGY IN LEARNING SCIENCE WITH SAINTIFIC APPROACH - Almunawaroh, Niza; Dewi, Irma Liliana Kusuma (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research aims to describe the use of PhET media in science learning, specifically on the topic of electricity, with the expectation that students can engage in active, independent learning, think critically, enhance digital literacy, and facilitate understanding of electrical circuit concepts. The research method used is qualitative, focusing on the application of PhET simulation media in science subjects, particularly electricity, for the fifth-grade students at SDN Sukasari. The subjects of this study are 16 fifth-grade students. The data obtained were analyzed using the Miles and Huberman data analysis model, which includes data collection, data reduction, data presentation, and conclusion drawing. The observations revealed that after implementing the PhET simulation media, students were able to engage in learning actively, independently, think critically, enhance digital literacy, and facilitate their understanding of electrical circuit concepts. However, there were challenges encountered, such as the instability of the internet connection at SDN Sukasari during the simulation process using PhET, which hindered the learning process since PhET is a digital media that requires an internet connection.